Managing “Perbadanan Tabung Pendidikan Tinggi Nasional” (PTPTN) loans among diploma students in UiTM Sarawak / Nurshaima Napis, Nur Fahidah Ali and Norfazila Jenal - Napis, Nurshaima; Ali, Nur Fahidah; Jenal, Norfazila (2010)
The act providing money in the form of a loan or capital is known as finance and something that everyone from governments to the private individual uses. It is also a branch of economics that studies the management of money and other assets. As information, management can be defined as the act or art of managing; the manner of treating, directing, carrying on, or using, for a purpose; conduct; administration; guidance; control; as, the management of a family or of a farm; the management of state affairs.